Monte Carlo simulations of adult and pediatric computed tomography exams: Validation studies of organ doses with physical phantoms. Issue 1 (18th December 2012) - Long, Daniel J.; Lee, Choonsik; Tien, Christopher; Fisher, Ryan; Hoerner, Matthew R.; Hintenlang, David; Bolch, Wesley E.
Abstract : Purpose: : To validate the accuracy of a Monte Carlo source model of the Siemens SOMATOM Sensation 16 CT scanner using organ doses measured in physical anthropomorphic phantoms. Methods: : The x‐ray output of the Siemens SOMATOM Sensation 16 multidetector CT scanner was simulated within the Monte Carlo radiation transport code, MCNPX version 2.6. The resulting source model was able to perform various simulated axial and helical computed tomographic (CT) scans of varying scan parameters, including beam energy, filtration, pitch, and beam collimation. Two custom‐built anthropomorphic phantoms were used to take dose measurements on the CT scanner: an adult male and a 9‐month‐old. The adult male is a physical replica of the University of Florida reference adult male hybrid computational phantom, while the 9‐month‐old is a replica of the University of Florida Series B 9‐month‐old voxel computational phantom. Each phantom underwent a series of axial and helical CT scans, during which organ doses were measured using fiber‐optic coupled plastic scintillator dosimeters developed at the University of Florida. The physical setup was reproduced and simulated in MCNPX using the CT source model and the computational phantoms upon which the anthropomorphic phantoms were constructed. Average organ doses were then calculated based upon these MCNPX results. Results: : For all CT scans, good agreement was seen between measured and simulated organ doses. For the adult male, the percent differences were within 16% for axial scans, and within 18% for helical scans. For the 9‐month‐old, the percent differences were all within 15% for both the axial and helical scans. These results are comparable to previously published validation studies using GE scanners and commercially available anthropomorphic phantoms. Conclusions: : Overall results of this study show that the Monte Carlo source model can be used to accurately and reliably calculate organ doses for patients undergoing a variety of axial or helical CT examinations on the Siemens SOMATOM Sensation 16 scanner.